Tigilanol Tiglate-Mediated Margins: A Comparison With Surgical Margins in Successful Treatment of Canine Mast Cell Tumours - De Ridder, Thomas; Reddell, Paul; Jones, Pamela; Brown, Graham; Campbell, Justine (Frontiers in Veterinary Science, 2021)
Tigilanol tiglate (TT) is a novel small molecule registered as a veterinary pharmaceutical for intratumoural treatment of canine mast cell tumours (MCTs). The drug has a multifactorial mode of action resulting in rapid destruction of the treated tumour by haemorrhagic necrosis and subsequent slough of the necrotic tumour to reveal a tissue deficit that is left to heal by second intention with minimal to no veterinary intervention. Here we introduce the concept of TT mediated margins, the calculated margin of tissue loss analogous to surgically applied margins to help clinicians conceptualise tissue deficits formed following tumour destruction by TT relative to surgical excision. We used data from 51 dogs that were recurrence-free 12 months after a single administered TT dose into a single target MCT <10 cm3 in volume in a randomised, controlled clinical trial in the USA. We calculated TT-mediated margins based on length of the longest axis of (i) the tumour prior to treatment and (ii) the maximum tissue deficit formed 7 to 14 days after TT treatment. We compared these TT-mediated margins for each tumour to two surgical approaches to MCT excision in general practice: modified proportional margins (with 2 cm upper limit) and 3 cm fixed margins. For most dogs, TT-mediated margins were less than half the length of the margins calculated for the two surgical approaches in removing the same tumour. There was a trend for TT-mediated margins to increase with increasing tumour volume. Nonetheless, even for the larger tumours in this study (>2 cm3 volume) 50% of TT-mediated margins were less than half the length of the two surgical margins. Eighteen cases were lower limb MCTs, sites often surgically challenging in veterinary practice. On these lower limbs, TT-mediated margins were less than half the length of the corresponding proportional margins in 56% of cases and larger than proportional margins in only 2 cases. This study suggests that, in many cases, smaller and more targeted margins could be expected when treating MCTs <10 cm3 volume with TT compared to surgical excision. TT-mediated margins are a novel approach to conceptualise tissue deficits after intratumoural TT treatment.